2019
DOI: 10.3390/su11133702
|View full text |Cite
|
Sign up to set email alerts
|

Loyalty Model Proposal of Travel Agency Customers

Abstract: Customer loyalty to a destination and accommodation services constitutes a frequent object of research; however, customer loyalty to travel agencies is rarely analyzed. The presented article is an attempt to fill in this research gap. Its purpose is to construct and verify the model covering the impact of the selected factors on the loyalty level of customers of travel agencies operating in Poland. The conceptualization of the loyalty model of travel agency customers (based on the European path-based EPSI mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…According to Karamata et al (2017), and Davidow (2003), speedy reply to the customer complaint cuts back the amount of negative word of mouth in perspective of the airline industry. Thus, service quality improvement depends on the ability of the airline to regularly meet passenger needs and desires and address their complaints promptly (Dudek et al, 2019;Prentice et al, 2017). By resolving customer complaints without a delay, the airline can benefit in order to achieve the competitive advantage, which enhances the service quality that would lead to the customer satisfaction and future economic aspects (Law, 2017).…”
Section: The Response Time Of Customer Handling and Customer Satisfactionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Karamata et al (2017), and Davidow (2003), speedy reply to the customer complaint cuts back the amount of negative word of mouth in perspective of the airline industry. Thus, service quality improvement depends on the ability of the airline to regularly meet passenger needs and desires and address their complaints promptly (Dudek et al, 2019;Prentice et al, 2017). By resolving customer complaints without a delay, the airline can benefit in order to achieve the competitive advantage, which enhances the service quality that would lead to the customer satisfaction and future economic aspects (Law, 2017).…”
Section: The Response Time Of Customer Handling and Customer Satisfactionmentioning
confidence: 99%
“…Customer satisfaction through immediate handling of customer complaints, loyalty of customers will be enhanced, which will be fruitful to retain existing customers and attract potential customers through positive word of mouth (Yao et al, 2019;Etemad-Sajadi & Bohrer, 2019;Oyewole et al, 2007;Fornell, 1992). Numerous studies have demonstrated that the immediate response time to respond to customer complaints not only retains the existing customer but also brings a new customer (Dudek et al, 2019;Prentice et al, 2017;Blodgett et al, 1995;Gummesson, 1994). Hence, based on the previous literature, we have formulated the following hypothesis:…”
Section: The Response Time Of Customer Handling and Customer Satisfactionmentioning
confidence: 99%
See 3 more Smart Citations